2022
DOI: 10.1002/crat.202200041
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effects of La/Sm Codoping on the Structural and High Temperature Thermoelectric Properties of n‐Type CaMnO3−δ Perovskite

Abstract: Oxide thermoelectric ceramics attract extensive research interest due to their excellent thermal stability, non-toxicity, cost-effectiveness, and earth-abundant constituent elements. In the present work, the authors study the effect of lanthanum (La) and samarium (Sm) co-doping on the structural, microstructural, and thermoelectric properties of CaMnO 3 ceramics. The X-ray diffraction (XRD) studies show an increase in unit cell volume with an increase in Sm concentration. A shift in Raman modes is observed, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Thermoelectric oxides that exhibit good n-type thermoelectric properties include Al-doped ZnO, [21][22][23] which is a widebandgap degenerate semiconductor, and the strongly correlated electron system CaMnO 3 with partially substituted cation sites. [24][25][26][27][28][29][30][31][32] No oxide with the same composition has shown ptype and n-type thermoelectric properties, as observed in the cases of Bi 2 Te 3 , PbTe, the Si-Ge alloy, skutterudites, and β-FeSi 2 . [1][2][3][4][5][6][7] However, some perovskite-type oxides in which transition-metal ions are in a mixed-valence state of trivalent and tetravalent ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermoelectric oxides that exhibit good n-type thermoelectric properties include Al-doped ZnO, [21][22][23] which is a widebandgap degenerate semiconductor, and the strongly correlated electron system CaMnO 3 with partially substituted cation sites. [24][25][26][27][28][29][30][31][32] No oxide with the same composition has shown ptype and n-type thermoelectric properties, as observed in the cases of Bi 2 Te 3 , PbTe, the Si-Ge alloy, skutterudites, and β-FeSi 2 . [1][2][3][4][5][6][7] However, some perovskite-type oxides in which transition-metal ions are in a mixed-valence state of trivalent and tetravalent ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, some perovskite-type oxides in which transition-metal ions are in a mixed-valence state of trivalent and tetravalent ions (e.g. n-type perovskite type oxides such as SrTiO 3 [33][34][35][36][37][38][39][40] or CaMnO 3 [24][25][26][27][28][29][30][31][32] and p-type perovskite-type oxides such as LaFeO 3 [41][42][43][44][45] or LaCoO 3 46-54)…”
Section: Introductionmentioning
confidence: 99%
“…The samples prepared in this study showed higher conductivity values than those of pristine CMO. 20 A twoorder increment s was obtained for L75D75 and L100D100. La 3+ and Dy 3+ ions contribute signicant changes in the electrical conductivity of CMO by facilitating the hopping between Mn 3+ and Mn 4+ ions.…”
Section: Xpsmentioning
confidence: 99%
“…14,15 J. W. Seo et al 16 studied the electric and thermoelectric properties of Y, Dy co-doped CMO. Furthermore, the thermoelectric properties of La, Er, 17 La, Ce, 18 La, Sr 19 La, and Sm 20 co-doped CMO were investigated in detail for gaining superior thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%